Effects of city-specific industry audit specialist and national industry audit specialist on audit quality and earnings conservatism, A case study of U.K. Public listed companies on London Stock Exchange - Peter, Mayola Wel (2017)
The evidence from the sample of U.K. public listed companies for the year 2014 show that city-specific industry specialist auditors and national industry specialist auditors demand a significant audit fee premium of 8.3% and 7% respectively. This empirical evidence infers that the reputation for an auditor industry specialisation in the U.K audit market pricing is the City specific audit specialist and national audit specialist. Basioudis and Francis (2007) also find a city specific industry leader having a higher audit premium of 15% in the U.K audit market pricing relative to other Big 4 auditors but no evidence among the national audit industry leaders. However, contrary to this study, my empirical results are in congruence to Kharudin and Basioudis (2018). Nonetheless, in this study, evidence of a JOINT audit specialist reputation shows 8.2% of the auditor fee premium. The empirical evidence of a joint audit specialist reputation is like the results of U.S and Australia’s joint audit market pricing. Despite this new finding, City specific specialist is still more reputable compared to national and JOINT leaders. This new proof confirms the claim of DeAngelo (1981) that audit specialist who demands higher audit fee premium have higher audit quality compared to the non-audit specialist. Having tested the pricing of the audit market in the U.K, the project moved to examine whether a relationship between city specific industry leaders and timelines and timely recognition of losses. The empirical results show that the city-specific leaders’ coefficient was positive but insignificant. The finding confirms that there was no positive relationship between the city specific industry audit specialist and earnings conservatism. There was no significant relationship also observed among the national auditors’ specialist and earnings conservatism. However, empirical finding shows that Industry audit specialist is positive and significantly associated with timeliness and timely recognition of losses only when the specialist is both National and city specific industry auditor specialist.